Sources of risks in livestock production and their management strategies in northern India - CHAND, SUBHASH; NARAYAN, PREM; CHAUDHARY, KHYALI R (The Indian Journal of Animal Sciences, 2023)
This study was undertaken to analyze the opinion on risks sources and their management strategies in livestock enterprises. Data collected through a field survey conducted in Haryana and Rajasthan in 2015–16 from 913 livestock farmers on structured schedule forms the basis of this paper. Rajasthan depicts dry and harsh tract and Haryana with assured irrigated, and both contribute significant share in milk production. The socio-economic and demographic factors did not vary significantly except milk yield, experience in dairy, annual income for different categories of farmers. Our observation indicated that livestock owner faced risks from different sources, viz. breeding, animal health, marketing, institutional and policy related. Further risk management strategies including better breed, animal health checkup, seeking advice of veterinary expert, friend consultations, forward selling contracts, maintenance of farm inventory, accessibility to different financial, extension and government institutions etc. were adopted to cope up with risks in livestock enterprise. The determinants of source of risks were significantly influenced by a number of socio-economic and demographic characteristics. The herd size had negative relation with extent of various risks. Rajasthan farmers face higher degree of risk than Haryana. Higher education status also indicated that the lover risks and other factors like knowledge level and milk yield indicated positive influence of source of risks means higher knowledge level and yield, reduce the risks. The policy makers and researchers should see the solutions and options to minimize the source of risks in livestock production and management.